Histone modifications and their roles in macrophage-mediated inflammation: a new target for diabetic wound healing - Wang, Jing; Feng, Jiawei; Ni, Yiming; Wang, Yuqing; Zhang, Ting; Cao, Yemin; Zhou, Mingmei; Zhao, Cheng (Frontiers in Immunology, 2024)
Impaired wound healing is one of the main clinical complications of type 2 diabetes (T2D) and a major cause of lower limb amputation. Diabetic wounds exhibit a sustained inflammatory state, and reducing inflammation is crucial to diabetic wounds management. Macrophages are key regulators in wound healing, and their dysfunction would cause exacerbated inflammation and poor healing in diabetic wounds. Gene regulation caused by histone modifications can affect macrophage phenotype and function during diabetic wound healing. Recent studies have revealed that targeting histone-modifying enzymes in a local, macrophage-specific manner can reduce inflammatory responses and improve diabetic wound healing. This article will review the significance of macrophage phenotype and function in wound healing, as well as illustrate how histone modifications affect macrophage polarization in diabetic wounds. Targeting macrophage phenotype with histone-modifying enzymes may provide novel therapeutic strategies for the treatment of diabetic wound healing.